Variability in peripheral rewarming after cold stress among 255 healthy Norwegian army conscripts assessed by dynamic infrared thermography. Issue 1 (1st January 2018) - Norheim, Arne Johan; Borud, Einar; Wilsgaard, Tom; De Weerd, Louis; Mercer, James B.
ABSTRACT: Exposure to cold climate is an inevitable consequence of military training in Norway. Adequate peripheral microcirculation in the extremities is important to maintain temperature, and to protect against freezing cold injuries. The aim of this study was to investigate the variability in skin rewarming ability. The study subjects consisted of 260 healthy Norwegian army conscripts, following a mild cold provocation test (hands immersed in 20°C water for 1 min) using dynamic infrared thermography (DIRT). Thermal images were obtained to investigate any differences in skin rewarming ability of the hand (fingers). DIRT took place under standardised and stable study conditions. Conscripts were characterised as either slow, intermediate or rapid rewarmers. While 90% could recover, partially or completely, within 4 min to the skin temperature values before the provocation test, 10% showed a slow rewarming pattern. In the slow rewarmers, the rewarming ability was correlated with a low average temperature of the hands prior to the cooling test. The healthy young army conscripts in this study showed a large variability in their rewarming ability following a standardised mild cold provocation test.